Impacts of COVID-19 on Work and Wages in Cox's Bazar : Part 1 - Rohingya Camps - World Bank (World Bank, Washington, DC, 2021)
This brief summarizes findings from rapid welfare tracking surveys in Cox’s Bazar. Two rounds of tracking surveys were implemented via phone interviews in 2020 to monitor the impacts of the COVID-19 crisis on labor markets, wages, and household coping strategies. The first round was conducted during the COVID-related lockdowns in April-May 2020. A second round was conducted from October-December 2020 (roughly 6 months after the government-imposed lockdowns). These rapid phone surveys are built on the Cox’s Bazar Panel Survey (CBPS), which is a multi-topic survey that focused on socio-economic outcomes and access to services. The baseline CBPS survey, implemented in March- August 2019, was designed to be representative of the recently displaced Rohingya population (displaced after August 2017) and the full Bangladeshi population in Cox’s Bazar. Within the host community, the survey included hosts from two strata: high exposure (HE, within 3 hours walking distance of a Rohingya camp) and low exposure (LE, more than 3 hours walking distance from a Rohingya camp) areas within the district. The overall sample size of the CBPS baseline was 5020 households (and two adults per household), split roughly equally across Rohingya camps and host communities, and within the latter, equally among HE and LE areas. Key modules of the baseline survey, including detailed labor market modules were administered to two randomly selected adults in each household. The first tracking survey re-interviewed 3,012 adults originally interviewed in the baseline, while the second survey interviewed 3,438 adults baseline adult respondents (1,554 adults in camps). This brief (Part 2) focuses on key findings among the Rohingya population in camps, with findings for the host community discussed in an accompanying brief (Part 1).